INFLUENCE OF THE HEIGHT ABOVE SEA LEVEL TO THE PHISIOLOGICAL-FUNCTIONAL CAPABILITES OF THE STUDENTS - Admira Koničanin; Arif Bronja-prof VSCG (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
The research was donl at the sample of 43 students of male sex at the average age of 22 years. The aim: the change of heart pulse frequeny was determined by the research. The hyupothesis that the increas went of the height above sea level has the influence to the students' cardio-vascular syustem werw determined by the research